The Impact of Expropriations on the Stock Prices of the Parent Companies: Sell on the rumor, buy on the news? (2016)
We measure the impact of warnings of expropriation and of forced divestments of pri- vate property on the stock prices of the parent company. We use a unique database of 116 events in 12 countries from 2005 to 2013. Our results show signi cant negative effects on the stock prices of different kinds of warnings; the largest effect is when the warning takes the form of a transitory permit revocation. In the case of forced divestments, we nd a signi cant negative impact when there is a permanent revocation of a permit. However, nationalizations seem to generate a positive market reaction.